Teaching children who are hard to reach : relationship-driven classroom practice - Marlowe, Michael J., 1947- (Corwin Press, 2013)
How do you move beyond traditional classroom management to create a learning environment that engages hardest-to-reach students - students who may be struggling due to emotional disturbances or disabilities or environmental circumstances? Michael Marlowe and Torey Hayden have the answer: through a relationship-driven classroom. Drawing on real-life stories, the authors shed new light on the challenges of working with hard-to-reach students and identify the key skills teachers need to build successful classroom relationships and facilitate learning for all.